The Effect Of Gold Price Fluctuations, Understanding Sharia Investment, And Inflation On Student’s Interest In Investing In Bank Syariah Indonesia’s Gold Installment Products - kholifah, Nur; Ayuningtyas Putri, Rizky Nur (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study aims to examine the effect of gold price fluctuations, understanding of sharia investment, and inflation on students' interest in investing in Bank Syariah Indonesia (BSI) gold installment products in the Greater Solo area. Using a quantitative approach, data collection was conducted through the distribution of questionnaires, and data analysis was performed using validity and reliability tests, classical assumptions, multiple linear regression, t-tests, f-tests, and the coefficient of determination (R2) with the help of SPSS software. This study involved a sample of students who were the main target of sharia investment products. The results show that gold price fluctuations and understanding of Islamic investment have a significant effect on investment interest (p = 0.001 and 0.013, respectively), while inflation has no significant effect (p = 0.172). These findings are in line with the rapid growth of BSI's gold installment program, which recorded a 177.42% YoY growth in financing to IDR 6.4 trillion and an 81% increase in gold customers to 336,000, dominated by the younger generation. Theoretically, these results reinforce the Theory of Planned Behavior (TPB) by confirming the dominance of behavioral and direct market factors over macroeconomic indicators among novice investors. The practical implications for BSI include strengthening sharia literacy and marketing strategies for gold price volatility to increase halal financial inclusion among students.